Effects of Different Processing Methods on the Antioxidant Activity of 6 Cultivars of Foxtail Millet - Lingyan Zhang; Jieying Li; Fei Han; Zhansheng Ding; Liuping Fan (Journal of Food Quality)
The total phenolic content (TPC) of millet was whole > dehulled > cooked > steamed and the bound phenolic content (BPC) was the main form. Compared with dehulled millet, the TPC, TFC, and phenolic acid contents were decreased significantly (P < 0.05). The retention rate of TPC of steamed millet ranged from 47% to 55% and cooked millet ranged from 55% to 79%. Additionally, the mean cinnamic acid content of cooked millet was 1.29 times as much as steamed millet. The antioxidant activity of millet was whole > dehulled > cooked > steamed. Therefore, cooked millet was a good choice for human.